The determinants of community college faculty attitudes toward unionization. - Goldey, Gregory Thomas. (My University, 1999)
This study examines unionization among faculty in higher education. Specifically, C. Wright Mills' theory of white-collar unionism is used to analyze the factors affecting attitudes toward unionization among community college faculty. Based on Mill's theory, the study attempts to answer the question, "What influence do union exposure, socio-economic background, political identification, and the experience of political organizational factors have on faculty attitudes toward unionization?" Much of the existing research on faculty attitudes toward unionization has focused on the effects of individual demographic characteristics (age, sex, race), and general job and organizational factors (job satisfaction, pay, and benefits) on faculty attitudes. However, this research has neglected to adequately examine the influences of individual socio-economic background, political identification, and the experience of the political organizational structure on attitudes (opportunities for advancement, power, and trust). The present study, by drawing on Mill's theory, addresses some of these inadequacies.

The labor movement has been the major source of empowerment for workers in the American economic and political system. However, union members generally are not representative of the labor force as a whole. Historically, the labor movement derived its strength from northern blue-collar workers with little representation from professional white-collar workers, including college and university faculty. While the 1970's experienced significant increases in faculty unionism (Garbarino, 1980), the rates remain significantly lower than the rates of other public employees. Unionization has not been widely used as a source of empowerment for faculty in higher education.

In the following study, data from a survey of 329 faculty teaching in the Kentucky community college system are used to study faculty attitudes toward unions and union membership. These surveys provide data regarding effects of demographic, political, economic, social, organizational, and attitudinal variables on union attitudes and membership in the KCCFA/AFT. The results show that on-going political and personal socialization factors, along with institution commitment are significant in shaping union attitudes and determining union membership.
Keywords: Labor unions Organizing Kentucky Public opinion.; Education, Higher.; Political Science, General.; Public opinion Kentucky.; Sociology, Industrial and Labor Relations.; Community college teachers Kentucky.; Labor unions Organizing Kentucky.; Community college teachers Labor unions Organizing Kentucky.; Economics, Labor.; Community college teachers Kentucky Attitudes.